Uncle Bob's animal stories - Devine, Bob.; Leeper, John H., 1949- (Chicago : Moody Press, 1986)
Twenty-three essays describes unique or useful characteristics God gave to the mongoose, trap-door spider, redheaded woodpecker, and other animals.
Keywords: Animals -- Religious aspects -- Christianity -- Juvenile literature; Animals